IMPLICIT VISUAL MESSAGES AND A DISCOURE DEMENSION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Visual representation of a phraseological image may convey implicit messages that are not directly expressed in text. This instantiation  is a case of concurrent visual and verbal allusion. Interesting aspect of visual representation is the visual development of figurative meaning.